(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Today’s teachers have an important task, such as educating intelligent, wellrounded people in an ever-changing era of innovation. This task requires the use of other sources of knowledge for teachers to be more self-seeking. The main goal of our teachers is to provide students with excellent knowledge, as well as to teach them a thirst for knowledge, self-research, and the ability to work. From this point of view, I think we can achieve our goal by perfectly organizing extracurricular activities in geography